Alteration of the Optoelectronic Properties of CuInS2 Quantum Dots via Colloidal Annealing - Dehm, Katharina; Zanetti, Alberto; Fett, Bastian; Mauritz, Vincent; Hamburger, Robert C.; Langford, Daniel; Guldi, Dirk Michael; Young, Elizabeth R.; Mandel, Karl; Crisp, Ryan (Crystal Growth and Design, 2024)
Colloidal semiconductor quantum dots (QDs) have tunable optoelectronic properties, thereby making them interesting materials for applications involving light-matter interactions. However, crystallographic and surface defects greatly impair their potential performance in devices. Herein, we present a straightforward approach to improve the quality of copper indium disulfide (CuInS2) QDs by adjusting the parameters of the colloidal synthesis. By the introduction of prolonged heating times after the nanocrystal growth has already gone to completion, defect states are partially removed. This “colloidal annealing” for varying time spans (from 5 up to 90 min) with longer annealing times correlating with a decreased ratio of emission from defect states compared to band edge emission, results in enhanced color purity. At shorter annealing times, the defects removed are mainly structural, indicated by the transition from mixed crystal phases to an almost phase-pure material. At longer annealing times, further improvements are linked to surface defect removal. Findings from transient absorption spectroscopy further confirm this trend by revealing a decrease in the intensity of a photoinduced absorption feature associated with sub-band gap states compared to the band edge bleach signal. These findings highlight the applicability of colloidal annealing as a straightforward strategy for direct material optimization during colloidal synthesis.<br

Enhancement of NiOx/Poly-Si Contact Performance by Insertion of an Ultrathin Metallic Ni Interlayer - Lange, Stefan; Fett, Bastian; Kabakli, Özde S.; Adner, David; Kroyer, Thomas; Bogati, Shankar; Schulze, Patricia S.C.; Herbig, Bettina; Hagendorf, Christian; Sextl, Gerhard; Mandel, Karl (physica status solidi (a), 2023)
Nickel oxide ((Formula presented.)) is a promising hole transport material for perovskite/Si tandem solar cells. Various silicon cell architectures may be used as bottom cells. The polycrystalline (poly-Si) (Formula presented.) tunnel diode is expected to be a high-efficiency interconnection scheme between the two subcells of monolithic tandems in p-i-n configuration with a high thermal budget, excellent passivation properties, and low contact resistivity. However, (Formula presented.) is then interfaced to poly-Si((Formula presented.)) and the chemical integrity of the interface due to the necessity of annealing treatments has to be questioned. For this purpose, the (Formula presented.) /poly-Si contact resistivity for different annealing temperatures is investigated between 100 and 500 °C, and two different (Formula presented.) deposition techniques, namely, wet-chemically applied and sputter-deposited (Formula presented.). The values of more than (Formula presented.) are obtained. The insertion of a nm-thin metallic Ni interlayer is shown to enable a tremendous decrease of the contact resistivity by 2–3 orders of magnitude. The formation of (Formula presented.) is proven by highly resolved (scanning) transmission electron microscopy ((S)TEM) coupled with energy-dispersive X-ray spectroscopy (EDXS). This interfacial engineering approach is expected to provide an effective way of improving the contact properties and integrability of (Formula presented.) into various tandem cell processes.
CRIS-Team Scopus Importer:2023-06-09
Keywords: contact resistivity; interface; nickel silicide; perovskite silicon tandem; silicon oxide; transmission electron microscopy

In Situ Crystallization of the Inorganic Lead-Free Halide Double Perovskite Cs2AgBiBr6 via Spray-Drying - Fett, Bastian; Kabaklı, Özde Ş; Sierra, Camila A.R.; Schulze, Patricia S.C.; Yoon, Songhak; Herbig, Bettina; Glunz, Stefan W.; Goldschmidt, Jan Christoph; Sextl, Gerhard; Mandel, Karl (ACS Applied Energy Materials, 2023)
Nontoxic, all-inorganic perovskite light absorbers have received a great deal of attention in recent years due to their potential to replace lead-containing perovskite materials in photovoltaics. Herein, the synthesis of the lead-free double perovskite Cs2AgBiBr6 as a powder, obtained via spray-drying, is reported to be capable of paving the way toward large scale production. Upon drying of the atomized precursor solution during spray-drying, the double-perovskite phase forms by in situ crystallization. The product that is obtained from spray-drying is compared to the one that is obtained from the so-called solution cooling method, which is often used for the absorber synthesis before dissolving the double perovskite powder for the thin film deposition. The absorber powder gained from the solution cooling method sets the benchmark for the spray-dried absorber powder. XRD and Raman analyses confirm the phase purity of the double perovskite, whereas UV-Vis spectroscopy confirms the desired bandgap. Furthermore, the absorber powders from both synthesis methods are successfully used to deposit and integrate absorber films in single-junction perovskite solar cells. Besides being introduced as an alternative synthesis route for the preparation of double perovskite absorber as dry powders independently from being applied onto a given substrate, the superior advantages of spray-drying compared to the conventional synthesis of the perovskite absorber via the solution cooling method are outlined: Spray-drying not only enables the synthesis of large amounts of perovskite absorber powders but also discards the usage of precarious solvents like concentrated hydrobromic acid and thus eliminates the need for extensive safety precautions. Hence, spray-drying may help the perovskite technology take the next step toward large-scale production and commercialization.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Cs; double perovskite; lead-free; perovskite solar cells; spray-drying

Supraparticles for Sustainability - Wintzheimer, Susanne; Reichstein, Jakob; Groppe, Philipp; Wolf, Andreas; Fett, Bastian; Zhou, Huanhuan; Pujales Paradela, Rosa; Miller, Franziska; Müssig, Stephan; Wenderoth, Sarah; Mandel, Karl (Advanced Functional Materials, 2021)
The indispensable transformation to a (more) sustainable human society on this planet heavily relies on innovative technologies and advanced materials. The merits of nanoparticles (NPs) in this context are demonstrated widely during the last decades. Yet, it is believed that the impact of particle-based nanomaterials to sustainability can be even further enhanced: taking NPs as building blocks enables the creation of more complex entities, so-called supraparticles (SPs). Due to their evolving phenomena coupling, emergence, and colocalization, SPs enable completely new material functionalities. These new functionalities in SPs can be utilized to render six fields, essential to human life as it is conceived, more sustainable. These fields, selected based on an entropy-rate-related definition of sustainability, are as follows: 1) purification technologies and 2) agricultural delivery systems secure humans “fundamental needs.” 3) Energy storage and conversion, as well as 4) catalysis enable the “basic comfort.” 5) Extending materials lifetime and 6) bringing materials back in use ensure sustaining “modern life comfort.” In this review article, a perspective is provided on why and how the properties of SPs, and not simply properties of individual NPs or conventional bulk materials, may grant attractive alternative pathways in these fields.
CRIS-Team Scopus Importer:2021-02-05
Keywords: nanomaterials; nanoparticles; supraparticles; sustainability

Thermal interdiffusion, microstructure and contact resistivity of NiOx/Ni/p+ poly-Si layer systems for perovskite/TOPCon tandem solar cells during annealing processes - Lange, Stefan; Fett, Bastian; Kabakli, Özde S.; Hähnel, Angelika; Adner, David; Kroyer, Thomas; Bogati, Shankar; Schulze, Patricia S.C.; Herbig, Bettina; Hagendorf, Christian; Sextl, Gerhard; Mandel, Karl (Solar Energy Materials and Solar Cells, 2023)
In a recently published article (Lange et al., 2023) [1], we envisioned and discussed a tandem solar cell concept based on a perovskite/TOPCon architecture in p-i-n configuration, that utilizes a p+/n+ polycrystalline silicon (poly-Si) tunnel junction and NiOx as hole transport material of the perovskite top cell. A direct contact of NiOx to p+ poly-Si is inevitable in such a device. We investigated that junction and reported how the contact resistivity of the NiOx/p+ poly-Si junction can be improved by orders of magnitudes by intentionally inserting a nm-thin metallic Ni interlayer at that interface through the formation of nickel silicide. In this contribution, we present comprehensive data on layer stack morphology, composition and interdiffusion and the impact on the measured contact resistivity based on (scanning) transmission electron microscopy (STEM) coupled with energy-dispersive X-ray spectroscopy (EDX), X-ray photoelectron spectroscopy (XPS) and time-of-flight secondary ion mass spectrometry (ToF-SIMS) of model samples as well as the real contact structures. Diffusion and reaction processes in the NiOx/Ni/p+ poly-Si layer stack are investigated during the annealing in the temperature range between 100 °C and 500 °C for varying Ni interlayer thicknesses of 0, 1.0 and 2.0 nm. Furthermore, two NiOx syntheses routes are investigated: sputter deposition (s-NiOx) and a wet-chemical approach (wc-NiOx). We correlate the improvement of contact resistivity for both systems and temperatures <300 °C in regard to contacts without metallic Ni interlayer with the observation of pinhole formation within the SiOz. We have observed that annealing the Ag/s-NiOx junctions above 300 °C under ambient air leads to rectifying contacts and high contact resistivities due to excessive interdiffusion of Ni, O and Ag.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Contact resistivity; Nickel oxide; Nickel silicide; Perovskite/TOPcon tandem solar cells; Tunnel diode

Thin film formation of wet chemically deposited NiOx and parasitic oxides at NiOx/Si interfaces during high-temperature annealing of selective contacts in perovskite/Si tandem solar cells - Lange, Stefan; Fett, Bastian; Hähnel, Angelika; Müller, Alexander; Herbig, Bettina; Naumann, Volker; Sextl, Gerhard; Mandel, Karl; Hagendorf, Christian (Solar Energy Materials and Solar Cells, 2022)
Wet chemically deposited NiOx is a promising hole-transport material in perovskite/Si tandem solar cells due to its high work function, chemical stability, and low cost. However, it requires subsequent annealing that may lead to the formation of SiOz at the Si interface to the bottom cell. These layers of nm thickness exhibit non-stoichiometric chemical composition and are detrimental for charge transport and passivation. In this contribution, we investigate the atomic and electronic structure as well as chemical properties of NiOx layers on Si after wet chemical deposition and annealing in air between 200 °C and 600 °C. For this purpose, photoelectron spectroscopy, X-ray diffraction, differential thermal analysis/thermogravimetric analysis coupled with Fourier transform infrared spectroscopy, time-of-flight secondary ion mass spectrometry, and electron-energy loss spectroscopy in a scanning transmission electron microscope are applied. After deposition and annealing at 200 °C, a mixed bulk phase consisting of NiOxHy is found which transforms to pure NiOx above 300 °C. A parasitic SiOz layer is observed at the NiOx/Si interface after this process, with a thickness of 3–4 nm after annealing at 500 °C. The impact of this interfacial layer for electrical current transport will be discussed concerning optimized performance and integrability in perovskite/silicon tandems.
CRIS-Team Scopus Importer:2022-04-08
Keywords: Annealing; Interfaces; Nickel oxide; Perovskites; Selective contacts; Tandem solar cells; Transmission electron microscopy

Ultrathin parasitic SiOzlayer formation at annealed wet-chemical NiOx/Si interfaces in Perovskite/Si tandem solar cells - Lange, Stefan; Fett, Bastian; Hähnel, Angelika; Müller, Alexander; Kabakli, Özde S.; Newcomb-Hall, Zachary; Herbig, Bettina; Schulze, Patricia S.C.; Naumann, Volker; Sextl, Gerhard; Mandel, Karl; Hagendorf, Christian (AIP Conference Proceedings, 2023)
NiOx is a promising hole-transport layer for perovskite/Si tandem solar cells due to its high work function and long-term bulk stability. Besides that, it should also be inert to reactions with materials in its proximity. NiOx will be interfaced to Si using a TOPCon bottom cell and the question about the chemical stability of this interface arises. In this contribution, we investigate the effect of air-annealing between 200 °C and 600 °C on the microstructural, electronical,chemical and electrical properties of the wet-chemical NiOx/Si interface with X-ray photoelectron spectroscopy (XPS), electron-energy loss spectroscopy in a scanning transmission electron microscope (STEM-EELS) and micro transfer length measurements (µ-TLM). A mixed bulk phase consisting of NiOxHy after annealing at 200 °C is found, which is converted to pure NiOx above 300 °C. The Fermi energy shifts correspondingly towards the NiOx valence band, indicating suitable p-selective properties. A nm-thin parasitic SiOz layer at the NiOx/Si junction is confirmed after an annealing step as low as 300 °C, reaching a thickness of 3-4 nm after annealing at 500 °C. This interfacial layer acts as a barrier for electrical current transport, greatly increases the contact resistivity and may hinder tandem integration.
CRIS-Team Scopus Importer:2023-08-18